Aortic valve calcium score and peri-prothesis leaks after transcatheter aortic valve implantation: a hint?. (4th February 2022) - Amador, A; Martins Da Costa, C; Calvao, J; Alves Pinto, R; Proenca, T; Carvalho, JM; Cabrita, A; Marques, C; Grilo, PD; Sousa, C; Macedo, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The first-line evaluation of aortic stenosis (AS) severity is Doppler echocardiography. Aortic valvular calcium score (AVCS) measured by tomography scans (TS) is useful in patients for whom echocardiography is not conclusive. For high-risk patients with symptomatic severe AS, transcatheter aortic valve implantation (TAVI) is an established procedure of treatment. The burden of aortic valve calcification has been associated with some TAVI related complications. Peri-prothesis leaks (PPL) are an important complication that may compromise TAVI net results and further refinements are required to predict high-risk patients.  Purpose: To access if there is an association between aortic valve calcium score and moderate to severe (mod-sev) peri-prothesis leaks immediately and 6 month after TAVI.  Methods: We performed a single-center, retrospective cohort study including patients who underwent TAVI with a preoperative standardised TS with AVCS available. Clinical and echocardiographic data were collected previously to TAVI (pre-TAVI) and at 6 months follow up (6M-FUP).  Results: A total of 187 patients were included, with 54% female and a mean age of 79.37± 9.029 year-old. Most patients had tricuspid aortic valve (95.7%); 5 patients had aortic bicuspidy and 3 had aortic valve bioprothesis. Considering left ventricular systolic function, the majority had conserved function (73.0%), the remaining had mild (9.7%), moderate (11.4%) or severe (5.9%) dysfunction.  Concerning the valve type, 73.3% had new generation prosthesis and the main valve used was the CoreValve Evolut Pro (33.7%). Also, 38.5% patients underwent balloon valve pre-dilation before implantation. In-hospital mortality was 2.7%. At 6M-FUP, 8 of 182 patients had dead.  The mean AVCS was 2851 ± 1524 AU (Agaston Units); 81.2% of women had AVCS > 1300 AU and 74.4% men had AVCS >2000 AU.  Comparing AVCS with the presence or absence of moderate to severe peri-prothesis leaks, no statistically significant difference was found immediately (no vs mod-sev leak, AS: 2758 ± 2308 vs 3621 ± 1376, p= 0, 13) and 6 months after the procedure (no vs mod-sev leak, AS: 2892 ± 2366 vs 3621 ± 1424, p = 0.15). Considering earlier (Portico, CoreValve Evolut R) vs newer valves (CoreValve Evolut Pro; Edward Sapiens 3; Accurate Neo), there was no statistically significant difference relating AVCS and PPL; however, in patients who had newer valves there was a trend to higher AVCS and moderate to severe leaks, both on the immediate (no vs mod-sev leak, AS: 2777 ± 2507 vs 3601 ± 1385, p = 0.07) and at 6 months (no vs mod-sev leak, AS: 2782 ± 2506 vs 3984 ± 1138, p = 0.06). No statistically significant difference was found when comparing pre-ballooning dilatation. Conclusion: Aortic calcium measured by Agatston score did not show an association with new moderate to severe peri-valvular leaks after TAVI. Nevertheless, it seems to be a trend for higher AS and moderate to severe peri-prothesis leaks when newer valves are implanted.